A social-ecological approach to characterize ecosystem services in the Ecuadorian Amazon - Neira-Brito, Francisco; Morales-Mite, Manuel A.; Aguilar-Melo, Adriana R.; Hull, Vanessa (Frontiers in Conservation Science, 2024)
Social-ecological approaches are necessary to understand complex systems in which humans are dependent on ecosystem services to support their livelihoods. We implemented structured interviews (n=89) to characterize the social-ecological interactions between colonists and ecosystem services in four social-ecological systems located in two southern Amazonian provinces of Ecuador. This characterization allowed us to describe the subsistence activities, ecological knowledge, and local institutions present in the studied social-ecological systems. Cattle ranching, agriculture, and hunting provide safety nets to generate moderate levels of cash for colonists to face unpredictable events. However, these subsistence activities, as well as ecological knowledge and local institutions are not adapted to the local dynamic of the Amazonian ecosystems. Through this characterization of the colonists' social-ecological interactions, we also identify the ecosystem services and disservices obtained. Thirteen ecosystem services were identified, six of which were generated within protected areas. Seven ecosystem disservices were also identified, none of them produced within protected areas. Our study shows the separation prevailing between humans and ecosystems in the social-ecological interactions of the colonists, and, at the same time, the key role of these maladapted interactions in their subsistence activities. This research contributes a qualitative strategy to assessing social-ecological interactions and illustrates the importance of the ecosystem services provided by the Amazon ecosystems to colonists.